Talon cusps - functional solution: a case report - Silva-Sousa, Alice Corrêa; Silva-Sousa, Yara Teresinha Corrêa; Tavella-Silva, Nathalia Cristina; Danelon, Marcelle (ARCHIVES OF HEALTH INVESTIGATION, 2021)
Talon cuspid is a rare dental anomaly that occurs more frequently in maxillary incisors and is defined as a projection in the area of the cincture of anterior teeth that extends from the cemento-enamel junction or the region of the cincture, following towards the incisal face. An eight-year-old female patient was referred to the University of Ribeirão Preto Pediatric Dentistry Clinic (UNAERP) with suspicion of a supernumerary tooth on the palatal surface of tooth 12. During clinical and radiographic examination she found the presence of a conical-shaped enamel projection that presented a communication with the tooth 12 cincture and was thus classified as a cusp talon. Initially, prophylaxis and removal of the accumulated bacterial plaque were performed, verification of premature contact with paper for the joint and wear with a spherical diamond tip. FluroShield sealant was then applied following an adhesive protocol indicated by the manufacturer. After the necessary occlusal adjustments were made. 30 days later, the patient returned for clinical follow-up, reconversion and repolishing of the sealant. The cuspid talon was diagnosed as Type I because it is morphologically well delineated and protrudes prominently from the palatal surface and extends at least halfway from the cemento-enamel junction to the incisal edge. It is recommended to seal the deep grooves to prevent caries. We can conclude that a rigorous clinical and radiographic examination leading to an early and accurate diagnosis is of extreme importance for the adoption of an adequate treatment.